2017
DOI: 10.1016/j.rmed.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Reducing socioeconomic inequalities in COPD care in the hospital outpatient setting - A nationwide initiative

Abstract: A systematic quality improvement initiative including regular audits, knowledge sharing, and detailed disease-specific recommendations for care improvement may increase the overall quality of care and considerably modify the substantial socioeconomic inequalities in COPD management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Research has shown that social disparities are best addressed by broad policies that may be beneficial not only for preventing COPD incidence but for decreasing health disparities for many other diseases and for all social strata ( Wilkinson & Pickett, 2009 ). A systematic quality improvement initiative in Denmark eliminated socioeconomic differences in COPD care during four years ( Tottenborg, Lange, Thomsen, Nielsen & Johnsen, 2017 ). In contrast, the privatizations of primary health care that have taken place in Sweden allocate health resources to affluent individuals ( Burstrom et al 2017 ) with lower risk and may therefore exacerbate such disparities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Research has shown that social disparities are best addressed by broad policies that may be beneficial not only for preventing COPD incidence but for decreasing health disparities for many other diseases and for all social strata ( Wilkinson & Pickett, 2009 ). A systematic quality improvement initiative in Denmark eliminated socioeconomic differences in COPD care during four years ( Tottenborg, Lange, Thomsen, Nielsen & Johnsen, 2017 ). In contrast, the privatizations of primary health care that have taken place in Sweden allocate health resources to affluent individuals ( Burstrom et al 2017 ) with lower risk and may therefore exacerbate such disparities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…However, the existence of small sociodemographic disparities and even smaller county-level disparities means that interventions should be proportionately more intense among sociodemographic strata with higher average risk of discontinuation, and to a lesser extent in counties with increased risk of discontinuation. One example of an efficient universal intervention is presented by Tottenborg et al, 64 who showed how a systematic quality improvement initiative managed to eliminate socioeconomic inequalities in COPD health care. Such universal incentives should be initiated in sociodemographic strata and counties with higher risk of discontinuation.…”
Section: Implications and Conclusionmentioning
confidence: 99%